Effects of Partial Sleep Deprivation on Information Processing Speed in Adolescence. (19th February 2016) - Cohen-Zion, Mairav; Shabi, Adi; Levy, Sigal; Glasner, Laura; Wiener, Avigail
Abstract: Objectives: Although chronic sleep loss is highly common among teens, few objective sleep studies have examined its effects on cognitive performance, and specifically on information processing speed (IPS), a measure of cognitive proficiency.Methods: Forty-five adolescents underwent four consecutive nights of monitored sleep restriction (6–6.5 hr/night) and four nights of sleep extension (10–10.5 hr/night), in counterbalanced order, and separated by a washout period. Following each sleep period, cognitive performance was assessed, at a fixed morning time, using a computerized neuropsychological battery including an IPS task, a timed test providing both accuracy and reaction time outcome measures.Results: Overall IPS performance was poorer in the restricted when compared to the extended condition. Increasing task load and pace were associated with increased accuracy for both sleep conditions. However, a significant pace by load interaction effect was only found in the extended condition, with post hoc tests showing that for medium and hard loads, IPS accuracies were better with increasing pace of task. Differences in IPS reaction times were not found between the sleep conditions. In addition, sleep-related changes in IPS indices were correlated with changes in executive function, motor skill, and attention performance.Conclusions: Adolescents' ability to process information may be especially vulnerable to sleep loss. Under ideal sleep conditions, however, they seem to be able to achieve optimal performance, particularly on more challenging problems. The functional implications of these findings may be particularly relevant to teens, who are often sleep deprived and are constantly required to process academic, social, and emotional input. ( JINS, 2016, 22, 388–398)